European Urban Growth - throwing some Economic Light into the Black Box - Paul Cheshire; Stefano Magrini (European Regional Science Association (ERSA), 2005)
This paper investigates growth differences in the urban system of the EU12 between the means of 1978/80 and 1992/94. Models in which growth of real GDP p.c. is the dependent variable perform well and make it possible to test significant hypotheses. The analysis supports the conclusion that systems of urban governance are strongly related to growth. The variables are formulated in a way which tests hypotheses derived from 'fiscal federalism' viewing growth promotion as the production of a local public good. Evidence is also found supporting a spatial adaptation of the endogenous growth model with the relative size of the university sector having a highly significant role in explaining growth differences. Careful testing for spatial dependence reveals that national borders are significant barriers to adjustment but including explicit spatial effects resolves the specification problems. Density of urbanisation in some parts of the EU12 produces a local 'growth shadow' effect consistent with dynamic agglomeration economies and with commuting flows having an important role in spatial economic adjustment processes where cities are densely packed. In addition, evidence is found supporting the conclusion that integration shocks in the EU favour core areas but that this effect tends to fade with time.
Keywords: 330